The synthetic protocol for α-bromocarbonyl compounds via brominations. Issue 18 (3rd May 2019) - Murata, Yumi; Takeuchi, Kentaro; Nishikata, Takashi
Abstract: α-Bromocarbonyl compound easily generates α-radicals in the presence of a proper initiator, such as copper salt. Recently, tertiary-alkylation reaction using α-bromocarbonyl compound as a tertiary alkyl source is recognized as one of the most important alkylation reactions. The reactions using α-bromocarbonyl compound are increasing, whereas synthetic methods for various functionalized α-bromocarbonyl compounds are not summarized. Generally, α-bromocarbonyl compounds can be synthesized from the corresponding carboxylic acids via α-bromo acid bromide, but the brominations of carboxylic acids are sometimes problematic. In this paper, we will report some technical information for a bromination and synthetic examples of representative α-bromocarbonyl compounds. Graphical abstract: Image 1